Community college instructors' experiences with post-baccalaureate reverse transfer students: a phenomenology - Smith, Scott R., author; Anderson, Sharon K., advisor (Colorado State University. Libraries, 2008)
This qualitative study examined the lived experiences of eight community college faculty. The goal of the research was to understand what it is like to teach community college classes with post-baccalaureate reverse transfer (PBRT) students in them. Using a phenomenological approach, the data was interpreted to develop an understanding of the essence derived from the participant's experience. Through the interpretation of the data, six master themes emerged: Participants' Description of PBRTs, Participants' Knowledge of PBRTs in Their Classrooms, Academic Capital Displayed by PBRTs in Participants' Classrooms, Dynamics and Interactions between PBRTs and non-PBRTs, Participants' Feelings of Teaching PBRTs, and Refining Teaching Styles to Fit PBRTs. These master themes provided the structure and meaning to the essence of the phenomenon, Professionals Working with Professionals - the Fluidity of Education. Participants' Description of PBRTs gave a portrayal of the PBRT student as the participants view them. The theme, Participants' Knowledge of PBRTs in Their Classrooms, allowed the participants to explain how they determined who PBRTs are and whether it mattered if they knew or not. The Academic Capital Displayed by PBRTs in Participants' Classrooms theme describes how the participants appreciate the academic capital PBRTs bring with them, as well as the seriousness, focus, and professional behaviors they display in class. The Dynamics and Interactions between PBRTs and Non-PBRTs theme describes the world of classes with both PBRTs and non-PBRTs. In this environment the evolution of relationships between the two groups of students and participants transpires. In the Participants' Feelings of Teaching PBRTs theme, participants shared their feelings about how it is a natural fit to teach PBRTs because of the connectedness of being professionals. The final theme, Refining Teaching Styles to Fit PBRTs, illustrates how the participants modified their teaching style so it was both equitable and fair to PBRTs and non-PBRTs. These six master themes were reduced to the essence of the participants' experiences of teaching PBRT students, Professionals Working with Professionals - the Fluidity of Education. It illustrates the professional relationships between the participant and PBRTs and the cyclical transference of knowledge, resulting in collaborative learning.
Keywords: community college; faculty; instructors; phenomenology; post-baccalaureate reverse transfer; postbaccalaureate; qualitative; reverse transfer students; community college education; vocational education; college administration; phenomenology